A New Inquiry into the Dialogue between Catholicism and Taoism’s Views of Life: Beginning with the Taoist Narrative of “to be Immortal through Death” - HUANG, Wei (Journal of Research for Christianity in China (JRCC), 2025)
Taoism and Christianity are often considered to be at the two poles of self-power v.s. other-power, present-life immortality v.s. after-life eternality, and even body v.s. soul. However, these views not only ignore the complicated theological aspects of both Taoism and Christianity but also hinder deeper dialogues between them. Begining with the Taoist narratives of “to be Immortal through Death”, this paper attempts to bridge the gap between the theology of Taoism and that of Christianity (mainly focusing on Catholicism), and to identify possible platforms for further dialogues between them: the theodicy, the theology of body, the paradox between predestinarianism and free will, and the problems of individualism, etc. These dialogues are fundamentally based on their shared beliefs with profound differences regarding the immortal or eternal life of the body which is a crucial part of their views of life. This paper concludes with a review on the history of the dialogues between Catholicism and Taoism in the Ming and Qing Dynasties, arguing that the dialogue between their views of life is the most urgent but weakest part of the current time but is believed to be in line for a new opportunity for development.
Keywords: Catholicism, Taoism, Views of Life